Misuse (and abuse?) of the concept of empowerment: the case of online offer of predictive direct-to-consumer genetic tests - Loredana Covolo; Sara Rubinelli; Grazia Orizio; Umberto Gelatti (Journal of Public Health Research, 2012)
Using the field of direct-to-consumer genetic tests as a case in point, this paper argues against the misuse of the term empowerment, and calls for a regulation of its usage. The misleading assumption under certain current usages of the concept of empowerment is that it is enhanced by the provision of health information. While the ‘information-empowerment’ correlation is misleading, if not wrong, the feeling of being empowered imposes an increasing burden of critical thinking on those people (patients and consumers) who have to evaluate that information and act for the benefit of their health.